Willingness To Pay Fair Trade Coffee In Malang East Java Indonesia - Ayu Wulandari Priyambodoi; A Yusuf Kholil (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2021)
Consumption of coffee in Indonesia has seen a significant rise in recent years. Malang is one city in Indonesia were produced coffee big volume. This research seeks to explore the determinants of coffee consumption in Malang with a specific focus on fair trade coffee. In a survey of 140 respondents in Malang City, consumers’ willingness to pay (WTP) for fair trade labeled coffee was measured. This research uses an interval regression to investigate individual demographic and consumption characteristic impacts on WTP. Results show that on average, consumers were willing to pay 22% more for a medium cup of fair trade coffee compared with traditional coffee. In addition, other variables that indicated a higher WTP included female consumers, consumers who made their own coffee, and consumers who planned to consume more coffee in the following year.